Association between inadequate antenatal care utilisation and severe perinatal and maternal morbidity: an analysis in the PreCARE cohort. (2nd August 2017) - Linard, M; Blondel, B; Estellat, C; Deneux‐Tharaux, C; Luton, D; Oury, JF; Schmitz, T; Mandelbrot, L; Azria, E; ,
Abstract : Objective: Because the effectiveness of antenatal care in reducing pregnancy complications is still discussed despite widespread recommendations of its use, we sought to assess the association between utilisation of recommended antenatal care and severe maternal (SMM) and perinatal morbidity (SPM). Design: Prospective cohort study. Setting: Four maternity units around Paris in 2010–2012. Sample: 9117 women with singleton pregnancies. Methods: Logistic regression models adjusted for maternal social, demographic and medical characteristics. Main outcome measures: Antenatal care utilisation was assessed by: (1) initiation of care after 14 weeks, (2) < 50% of recommended visits made, according to gestational age, (3) absence of the first, second or third trimester ultrasounds, (4) two modified Adequacy of Prenatal Care Utilisation indexes, combining these components. The two main outcomes were composite variables of SMM and SPM. Results: According to the modified Adequacy of Prenatal Care Utilisation index, 34.6% of women had inadequate antenatal care utilisation; the incidence of severe maternal morbidity (SMM) was 2.9% and severe perinatal morbidity (SPM) 5.5%. A percentage of recommended visits below 50% (2.6% of women) was associated with SMM [adjusted odds ratio (OR) 2.40 (1.38–4.17)] and SPM [aOR 2.27 (1.43–3.59)]. Late initiation of care (17.0% of women) was not associated with SMM or SPM. Failure to undergo the recommended ultrasounds (16, 17 and 22% of women) was associated with SPM. Inadequate antenatal care utilisation according to the index was associated with SPM [aOR 1.37 (1.05–1.80)]. Conclusion: Inadequate antenatal care utilisation is associated with SMM and SPM, to degrees that vary with the component of care and the outcome considered. Tweetable abstract: Inadequate antenatal care utilisation is associated with severe maternal and perinatal morbidity. Tweetable abstract: Inadequate antenatal care utilisation is associated with severe maternal and perinatal morbidity.